Pengaruh Pembiayaan Mudharabah dan Akuntansi Pembiayaan Musyarakah Terhadap Profitabilitas Bank Syariah Indonesia - Alfina Agustin; Uly Mabruroh Halida (Shafin: Sharia Finance and Accounting Journal, 2022)
The financing are to get or providing funds for business improvement. Profitability is the rate of knowing the companies ability to generate profits during a certain period. The purpose of this study is to determine whether there is an effect of Mudharabah Financing and Musyarakah Financing Accounting on Profitability, either simultaneously or partially. This study uses a quantitative approach with the type of secondary data. The sample used is the quarterly financial statements of all bank that are merged into Indonesian Islamic Banks registered with the OJK for the 2016-2020 period as many as 60 financial reports. The results of this study indicate that simultaneously Mudharabah Financing and Musyarakah Financing Accounting has significant effect on Profitability at Indonesian Islamic Bank, because the value of fcount > ftable is 15,632 > 3,16. Based on partial testing, Mudharabah Financing and Musyarakah Financing Accounting have significant effect on Profitabilities at Indonesian Islamic Bank due to the tcount value of each variable > ttable, namely tcount of 5,402 (Mudharabah), dan 4,794 (Musyarakah) with a value of ttable = 2,002.